Basic Management in Managing Boarding School - Akhmad Afroni (Universal Institute of Professional Management, 2020)
Boarding school management has many day-to-day challenges. They are responsible for academic excellence as well as caring for the well-being of students 24 hours a day. Ensuring that all staff are working together and sharing information is key to providing the best possible level of care for pupils. Cloud-based software can go a long way to alleviating some of the difficulties around keeping students safe and sharing relevant information amongst staff. There’s a lot of information out there about what a boarding school is and how students can benefit from attending one. There are so many different types of boarding school – from prep academies to military or religious school. While it’s clear there is no one-size-fits-all model, there are some characteristics that we feel create a beneficial learning environment.